Development of Some Potentially Active Nitrogen Heterocycles: Exploring the potential of nitrogen heterocycles in drug development (Journal of Advances and Scholarly Researches in Allied Education, 2019)
In the synthesis of new and improved drugs, Heterocyclic chemistry has its most significant mission, its successful introduction in clinical trials, which exhibits a strong advantage over a drug already established. The benefits are limited in terms of improvement in biological activity, lower side effects, lower toxicity and mostly lower production costs. Heterocyclic chemistry is a chemical branch that deals with the synthesis, properties and application of a cyclic or ring compound that, as part of a loop or ring, has two distinct elements. The widespread emergence of bacterial and fungal resistant strains is becoming a major public health problem. This means that new antimicrobial agents with novel mechanisms of action need to be created. Continuous attempts to design new antimicrobials continue to be one of the greatest obstacles in the production of medicines. An significant and daunting issue is still the management of infectious diseases. There are areas of current and increasing interest, despite the quest for new antimicrobial agents, and several compounds have been synthesised to this end. One of the many reasons justifying the rapid increase in interest in research on new and more effective agents is increasing bacterial, fungal and cancer resistance to currently available antibacterial, antifungal and anticancer agents. Organic compounds are the primary source of the production of drugs today, natural or synthetic together in the form of various heterocycles with nitrogen as an ingredient. These heterocyclic compounds are from natural origin, i.e. from plant and animal origin, and another is from laboratory synthesis whose composition is close to that of natural origin. Nitrogenic organic compounds are of considerable significance not only because of their widespread natural occurrence, but also because of their wide variety of applications in the industries of pharmaceuticals, dyes, agrochemicals, etc. The continuing interest in the synthesis of heterocyclic nitrogen compounds is largely due to their increased biological activity and to the potential creation of new molecules with specific properties. A major class of nitrogenous compounds in organic and medicinal chemistry are thaizoles, indazoles, sulfonamides, amides, oxazines, pyrazoles and their derivatives.